2016
DOI: 10.1007/s10103-016-2114-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and biochemical effects (CTX-II, MMP-3, 8, and 13) of low-level laser therapy (LLLT) in chronic osteoarthritis in Al-Kharj, Saudi Arabia

Abstract: Inflammation of synovial membrane and degeneration of articular cartilage in osteoarthritis (OA) lead to major changes in joint space width (JSW) and biochemical components such as collagen-II telopeptide (CTX-II) and matrix metallo protineases (MMP-3, 8, and 13). Low-level laser therapy (LLLT) is thought to have an analgesic effect as well as biomodulatory effect on microcirculation and cartilage regeneration in animal studies. The objective of this study was to examine the analgesic and biochemical effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The analgesic and anti-inflammatory effects of LLLT are associated with elevating of pain threshold and inhibiting the transmission of A-δ and C fibers that combined with suppressed peripheral nociceptors, increased hydroxyindoleacetics, decreased inflammatory cytokines such as IL-1 β , IL-8, and TNF- α , and reduced prostaglandin levels [ 30 ]. Moreover, LLLT inhibits pain through enhancing the secretions of peripheral endogenous opioids [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic and anti-inflammatory effects of LLLT are associated with elevating of pain threshold and inhibiting the transmission of A-δ and C fibers that combined with suppressed peripheral nociceptors, increased hydroxyindoleacetics, decreased inflammatory cytokines such as IL-1 β , IL-8, and TNF- α , and reduced prostaglandin levels [ 30 ]. Moreover, LLLT inhibits pain through enhancing the secretions of peripheral endogenous opioids [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ] have also shown that PBM is a promising drug-free tool for inflammatory diseases and arthritis ( Table 2 ).…”
Section: New Introspections and Perspectives On Photobiomodulationmentioning
confidence: 99%
“…Surgical and non-surgical approaches have shown a positive improvements in PTOA following ACL injury. However, the neuromuscular control and muscle properties over the joint are not obtained properly and the H/Q imbalance also persists for a long time after injury 12 . Recent studies observed that integrated rehabilitation training programs improve neuromuscular control, muscular symmetry, cartilage morphology and lower the levels of inflammatory reactions in patients with PTOA following ACL injury 13 .…”
Section: Introductionmentioning
confidence: 99%